Self-realization in Green’s Looking for Alaska: An Existentialist Critique - Kiramatullah; Samina Ashfaq (University of Chitral Journal of Linguistics and Literature, 2024)
This research paper explores self-actualization within John Green’s novel, "Looking for Alaska," from the existentialist perspective. Existentialism, a philosophical framework, posits that humans must forge their meaning and grapple with rational decision-making in an inherently irrational and meaningless world. Central to this theory is Jean-Paul Sartre’s concept that existence precedes essence, emphasizing freedom as the fundamental element that imbues human life with significance. Green’s literary works often echo existentialist themes, portraying characters who embark on journeys of self-discovery amidst life’s adversities. In "Looking for Alaska," teenage protagonists confront daunting challenges as they navigate the complexities of existence, striving to carve out individual identities in the face of existential uncertainties. Miles pursues the elusive "Great Perhaps," symbolizing a quest for novelty and significance, while Alaska seeks solace in a life of independence and recklessness, grappling with personal traumas. This study employs Sartre’s existentialist framework to dissect Green’s portrayal of existential themes in "Looking for Alaska," shedding light on the characters’ pursuit of self-actualization amidst life’s existential quandaries.